Spatial dispersion of index components required for building invisibility cloak medium from photonic crystals. (21st March 2018) - Jamilan, Saeid; Semouchkin, George; Gandji, Navid P; Semouchkina, Elena
Abstract: The opportunities to use dielectric photonic crystals (PhCs) as the media of cylindrical invisibility cloaks, designed using transformation optics (TO) concepts, are investigated. It is shown that TO-based prescriptions for radial index dispersion, responsible for turning waves around hidden objects, can be dropped if the PhC media support self-collimation of waves in bent crystals. Otherwise, to provide prescribed anisotropy of index dispersion, it is possible to employ PhCs with rectangular lattices. It is found, however, that at acceptable cloak thicknesses, modifications of crystal parameters do not allow for achieving the prescribed level of index anisotropy. This problem is solved by finding the reduced spatial dispersion law for the radial index component, which is characterized by decreased against TO-prescriptions values near the target and increased values in outer layers of the cloak. The cloak utilizing reduced prescriptions for indices is shown to perform almost as efficiently as a TO-based cloak, in terms of both wave front restoration behind the target and reducing the total scattering cross-width of the target.